Memahami Sejarah Bangsa Dalam Politik Diplomasi Indonesia-Belanda - Herdian Tria Wulan Sari; Dini Andreswari Prianbudi; Nursalim; Agus Budianto (Philosophiamundi, 2024)
This article examines the historical context of Indonesian-Dutch diplomatic relations, focusing on the role of historical understanding in shaping current diplomatic practices. It argues that a nuanced understanding of shared history, including conflicts and collaborations, is crucial for promoting constructive and mutually beneficial relationships. This article analyzes key historical events, including the Dutch colonial period, the Indonesian struggle for independence, and post-independence relations. It highlights the importance of reconciliation, dialogue, and a commitment to shared values for building a more robust and sustainable future for both nations.